Screening and identification of vascular endothelial cell targeting peptide in gastric cancer through novel integrated in vitro and in vivo strategy - Yan-ting Zhang; Sheng-hui Wang; Li Zhao; Hui-min Wang; Lin Wang; Rong-rong Shi; Si-chao Liang; Bao-feng Li; Bei Chen (BMC Cancer)
Abstract Purpose Antiangiogenesis therapy has become a hot field in cancer research. Given that tumor blood vessels often express specific markers related to angiogenesis, the study of these heterogeneous molecules in different tumor vessels holds promise for advancing anti-angiogenic therapy. Previously using phage display technology, we identified a targeting peptide named GX1 homing to gastric cancer vessels for the first time. However, GX1 also showed some non-specific binding with normal gastric vessels, which can lead to toxic side effects on normal endothelial cells. Therefore, we urgently need to adopt new screening strategies to avoid non-specific binding to normal vessels and obtain gastric cancer vascular targeting peptides with higher specificity. Methods In this study, we designed a new strategy which combined “positive screening” in vivo and “negative screening” in vitro for the first time. An in vivo positive screening was conducted using tumor bearing nude mice to identify peptides that were specifically enriched within the vasculature of gastric cancer. Concurrently, an in vitro negative screening process was conducted on normal vasculature endothelial cells, including human umbilical vein endothelial cells (HUVECs) and human microvascular endothelial cells (HMVECs), to eliminate peptides binding to normal vasculature. After four rounds of iterative screening, a targeting peptide specifically targeting gastric cancer vasculature was obtained. In addition, an in vitro co-culture model by culturing HUVEC in tumor conditioned medium (Co-HUVEC) was established to investigate the affinity of these peptides. The targeting peptide was labeled with fluorescein isothiocyanate (FITC) for competitive and inhibitory assays. Results Blood vessel density analysis confirmed redundant capillary vessels in the xenografts, indicating that the mouse model was suitable for positive screening. Following four rounds of panning, a significant enrichment for phages specifically binding to gastric cancer vasculature was observed, with minimal binding to normal endothelial cells. The peptide CNTGSPYEC exhibited the highest reproducibility. In vitro immunofluorescence staining confirmed that the peptide CNTGSPYEC could specifically enrich in Co-HUVECs while showing no binding to normal vascular endothelial cells. In vivo immunofluorescence staining revealed that the peptide CNTGSPYEC could only bind to vascular endothelial cells specifically in gastric cancer but show no non-specific binding with normal tissue. Competitive and inhibitory assay also verified the targeting characteristics of the peptide with the fluorescence intensity of 17.13. As the concentration increases, the competitive inhibition rate can be incrementally raised to 93% (p < 0.05). Endothelial tube formation assay indicated that the peptide could suppress neovascularization, with the microvessel count reducing by 40% (p < 0.05). Furthermore, Cell Counting Kit-8 assay (CCK8) showed that the targeting peptide could partly inhibit cell proliferation of Co-HUVEC (61.7%). Conclusion Our novel strategy of the combined in vitro and in vivo screening outperforms previous methods that relied solely on negative/positive screening. In vivo and in vitro test confirmed the high targeting characteristic of the new peptide. Therefore, the peptide CNTGSPYEC may be a potential candidate in diagnosis and anti-angiogenesis therapy of gastric cancer. Our further exploration employs it as a vehicle for mediating drug accumulation in gastric cancer tissue.